IMPLEMENTASI MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA ISLAM - Rudi Ahmad Suryadi (Universitas Pendidikan Indonesia, 2022)
AbstractIslamic Teaching is also an instrument of learning in the formation of moderate attitudes and behavior in religion. The content of teachings on tolerance, multiculturalism, and differences in understanding in a religious context is an important instrument in the content of Islamic Teaching. Ideally, the learning of Islamic Teaching is closely related to the internalization of this religious moderation. Mainstreaming religious moderation in Islamic Teaching can be done through several strategies, namely strengthening the paradigm of moderation, curriculum, and learning. These three strategies are related to each other in the development of policies for the application of strengthening moderation in the context of Islamic Teaching. The policy of the Directorate of Islamic Teaching at the Ministry of Religion Affairs of the Republic of Indonesia in the realization of this moderation is considered important to lead to the mainstreaming of the formation of moderate attitudes and behavior supported by moderate religious understanding. In addition, religious moderation can be implemented in religious extracurricular activities.Keywords: Religious Moderation, Islamic Religious Education, Learning Implementation, Islamic Education, Moderation AttitudesAbstrakPendidikan Agama Islam juga menjadi instrumen pembelajaran dalam pembentukan sikap dan perilaku moderat dalam beragama. Muatan ajaran tentang toleransi, multikultural, dan perbedaan faham dalam konteks keagamaan menjadi instrumen penting dalam konten Pendidikan Agama Islam. Secara ideal, begitu pula pembelajaran Pendidikan Agama Islam berhubungan erat dengan internalisasi moderasi beragama ini. Mainstreaming moderasi beragama dalam Pendidikan Agama Islam dapat dilakukan melalui beberapa strategi, yaitu penguatan paradigma moderasi, kurikulum, dan pembelajaran. Ketiga strategi ini berkaitan satu sama lain dalam pengembangan kebijakan penerapan penguatan moderasi dalam konteks Pendidikan Agama Islam. Kebijakan Direktorat Pendidikan Agama Islam Kementerian Agama RI dalam perwujudan moderasi ini dipandang penting mengarah pada mainstreaming pembentukan sikap dan perilaku moderat yang didukung oleh pemahaman keagamaan yang moderat. Selain itu, moderasi beragama dapat diimplementasikan pada kegiatan ekstrakurikuler keagamaan.Kata Kunci : Moderasi Beragama, Pendidikan Agama Islam, Implementasi Pembelajaran, Pendidikan Islam, Sikap Moderat